KETERAMPILAN TEKNIK DASAR SEPAK BOLA USIA 10-12 TAHUN SSB KODAM XII TANJUNGPURA - Nurmali Nurmali; Ahmad Atiq; Muhammad Fachrurrozi Bafadal (Universitas Tanjungpura, 2021)
ABSTRACTThe problem in this study is how the level of basic soccer technical skills at the Tanjungpura Kuburaya Kodam football school. The research method used is a survey method with a basic soccer technique test consisting of passing, traping, dribbling, shoting and heading with a research sample of 20 students in the age category of 10-12 years. In soccer games, the most basic passing techniques are in the medium category, namely the frequency of 13 students with a percentage of 65%. in the soccer game with the most basic traping techniques in the medium category, namely the frequency of 14 students with a percentage of 70%. In the basic heading technique game, the highest number of categories is the frequency of 14 students with a percentage of 70%. In the basic technique game of soccer dribbling, the highest number of students is in the medium category with a frequency of 10 students with a percentage of 50%. In the basic technique game of shooting soccer, the highest number of students is in the medium category with a frequency of 10 students with a percentage of 50%.Keywords: Basic Football Technical Skills, Kodam Football School